Critical Analysis of Health Security Policies: Bridging Gaps in Global Preparedness - Saq, Jaber Salem S Abu; Al-Hababi, Mohammed Saad Ali; M, Alyami, Fahad Salem; Alsalem, Ali Hamad Mohammed; M, Alsalem, Abdullatif Hamad; B, Alsalem, Mosa Hussain; yami, Ali Hamad AL; Aldawais, Hamad (Journal of Ecohumanism, 2024)
The facets of COVID-19 have exposed deep structural flaws in the world health systems, weaknesses, and disparities of preparedness. The following paper looks at the various policies used in the global health security system before highlighting pitfalls observed and the strategies that can be used to solve the problem. Examining historical crises such as COVID-19 and the 2014-2016 Ebola, the study also reveals intrinsic weaknesses in the system, including disparity of funds distribution and lack of warnings compliance mechanisms. In applying qualitative and quantitative research, this paper recommends equity, collaboration, and technology as some of the gaps that need to be closed. Recommendations for rebuilding a more resilient world target investments in international equity and balanced resource distribution, responsible technological advancement, and well-developed international systems.